Screening and evaluation of ethanolic extract from Casuarina equisetifolia inflorescence on isolated chick rectum, frog rectum and frog rectus abdominus muscle for identification of muscarinic and nicotinic receptor’s action - Umamaheswar Rao, O.; Chinna Eswaraiah, M. (Journal of Drug Delivery and Therapeutics, 2018)
The present experiments were undertaken to justify the use of an ethanolic extract from inflorescence of Casuarina equisetifolia, Family: Casuarinaceae, influencing the nicotine responses on isolated chick rectum and frog rectum (Smooth Muscles) and frog rectus abdominus muscle (Skeletal Muscle). The isolated tissues were mounted in organ bath filled with physiological solution and was suitably aerated. After equilibration, responses were taken to different doses of nicotine (log doses) till a ceiling response was obtained. A sub-maximal dose of nicotine was selected and responses to this dose was taken and ensured that there is reproducibility of response. The drum was allowed to move for 1min., different concentrations of extracts into the organ baths were added and allowed to act for 1min without flushing the baths, then the sub-maximal dose of nicotine was added and allowed to act for 1min. this procedure was repeated (without extract) till the original response was obtained. The inference drawn from these experiments, the ethanolic extract of inflorescence of Casuarina equisetifolia antagonised the action of nicotine on isolated chick rectum, relaxed the effect of nicotine on frog rectum and it potentiated the effect of nicotine on frog rectus abdominus muscle. The nicotine receptors of rectus abdominus is activated, perhaps by the prevention of hydrolysis of acetylcholine by the extract. Based on the results obtained from the isolated chick rectum the ethanolic extract is having antinicotinic activity and it may act on the nicotinic acetylcholine receptors (nAChRs) as well as muscarinic acetylcholine receptors (mAChRs) on other isolated tissues. The extract might contain ganglionic blocking activity or non-specific activity or membrane stabilising activity also. Keywords: Nicotine, Ethanolic extract, Inflorescence of Casuarina equisetifolia, Isolated Chick Rectum, Isolated Frog Rectum and Isolated Frog Rectus Abdominus Muscle.